Twisting Clay : Creative Research to Explore the Complex Rheology in Ceramic Extrusion - Jorgensen, Tavs; Lightfoot, Sonny Lee (FormAkademisk, 2023)
This paper details practice-based research exploring new creative possibilities involving the ceramic extrusion process. The paper begins by providing a short overview of the extrusion technique, its characteristics and some contextual coverage of the process. The paper then describes how both tacit knowledge and theoretical material understanding have been used to overcome technical challenges through iterative research cycles and how, ultimately, the aesthetic qualities of the extrusion process have been used to develop a body of creative work. A key theme of the research is how digital fabrication technologies can be used in toolmaking scenarios to deliver innovation with a process that has long been used in craft ceramics but has remained somewhat underutilised.